2016
DOI: 10.3389/fpsyt.2016.00184
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aryl Hydrocarbon Receptor-Related Gene Variants with the Severity of Autism Spectrum Disorders

Abstract: Exposure to environmental chemicals, such as dioxin, is known to have adverse effects on the homeostasis of gonadal steroids, thereby potentially altering the sexual differentiation of the brain to express autistic traits. Dioxin-like chemicals act on the aryl hydrocarbon receptor (AhR), polymorphisms, and mutations of AhR-related gene may exert pathological influences on sexual differentiation of the brain, causing autistic traits. To ascertain the relationship between AhR-related gene polymorphisms and autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…As TNF and other pro‐inflammatory cytokines can increase indoleamine 2,3‐dioxygenase (IDO), leading to tryptophan being driven down the kynurenine pathway and away from serotonin and melatonin synthesis, 4 it will be important to determine IDO and kynurenine pathway products in correlation with TNF, and aMT6s in future research. Given the alterations in the kynurenine pathway in ASD, 69 and the ability of kynurenine and kynurenic acid to activate the aryl hydrocarbon receptor (AhR), a susceptibility gene for ASD severity, 70 the integration of the kynurenine pathway, AhR, and their impacts on neuronal and immune system function with the immune‐pineal axis will be important to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…As TNF and other pro‐inflammatory cytokines can increase indoleamine 2,3‐dioxygenase (IDO), leading to tryptophan being driven down the kynurenine pathway and away from serotonin and melatonin synthesis, 4 it will be important to determine IDO and kynurenine pathway products in correlation with TNF, and aMT6s in future research. Given the alterations in the kynurenine pathway in ASD, 69 and the ability of kynurenine and kynurenic acid to activate the aryl hydrocarbon receptor (AhR), a susceptibility gene for ASD severity, 70 the integration of the kynurenine pathway, AhR, and their impacts on neuronal and immune system function with the immune‐pineal axis will be important to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…Total neuroprotective metabolites such as picolinic acid (PA), a metabolite of the KP, are decreased in ASD patients despite an excess of QA production (Lim et al, 2016). Moreover, AhR signaling might also be involved, as polymorphisms in the gene encoding AhR nuclear translocator (ARNT), which binds and facilitates AhR functions, are associated with ASD severity (Fujisawa et al, 2016).…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%
“…In contrast, the hippocampi of bipolar disorder patients displayed marked changes in glucose metabolism. 72 Another study found an association between AhR-related gene variants and ASD severity 73 (for more details, see Figure 2 ).…”
Section: Potential Communication Pathways Between Gut Microbiota and The Brainmentioning
confidence: 99%